Lithium ion battery

By setting a double-layer positive electrode active material layer and adding lithium supplementary material in the positive electrode of the lithium-ion battery, the problems of poor performance of spinel lithium manganese oxide in the 3V range and insufficient high-temperature cycle stability are solved, and the stable operation and high energy density of the lithium battery in the 3V-4V range are achieved.

CN119542512APending Publication Date: 2025-02-28SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783731.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The spinel lithium manganese oxide has poor performance in the 3V range, making it difficult to use as an effective positive electrode material within the voltage range, and a rapid voltage drop will occur in the 3V to 4V range, resulting in discontinuity of the voltage curve, which may cause insufficient output in this range. In addition, its cycle stability is poor under high temperature conditions and capacity attenuation is prone to occur.

Method used

A double-layer positive electrode active material layer is provided in the positive electrode of the lithium-ion battery, and the thickness ratio and mass ratio of the second positive electrode active material layer and the first positive electrode active material layer are controlled. The synergistic effect between lithium-rich manganese and lithium manganate is achieved through the double-layer positive electrode active material layer, thereby improving the performance of the lithium battery and enhancing structural stability. At the same time, lithium supplement material is added to the positive electrode to improve the rate performance and electrochemical stability of the battery.

Benefits of technology

Through the design of the double-layer positive electrode active material layer, the lithium battery can operate stably within the 3V range and avoid a sharp pressure drop within the 3V-4V range, which improves the overall performance and structural stability of the battery and extends the battery life. The addition of lithium supplement material further improves the energy density and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a lithium ion battery in the technical field of lithium batteries, in particular to a solid-state lithium ion battery. A double-layer electrode structure is adopted to achieve the synergistic effect of lithium-rich manganese and lithium manganate, the double-layer positive electrode active material layer is arranged in the positive electrode, the thickness ratio and the mass ratio of the second positive electrode active material layer to the first positive electrode active material layer are controlled, and meanwhile, the lithium supplementing material is added into the positive electrode, so that the lithium-rich manganese-lithium battery is obtained. And the rate capability and the electrochemical stability of the battery are improved. Specifically, the positive electrode includes a positive electrode current collector, a first positive electrode active material layer including spinel manganese oxide, and a second positive electrode active material layer including lithium manganese oxide of a layered structure and a third positive electrode active material. Through the design, the performance of the lithium battery is remarkably improved, the structural stability is enhanced, and the cycle life of the lithium battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery. Background Art

[0002] Spinel lithium manganese oxide has attracted much attention and been widely used as a cathode material for lithium-ion batteries in recent years. Its unique spinel structure gives it high conductivity and fast ion diffusion ability, making it excellent in high-power applications. In addition, the raw materials of spinel lithium manganese oxide are abundant and low in cost, which has significant economic advantages compared to other cathode materials such as lithium cobalt oxide and lithium nickel cobalt manganese oxide.

[0003] However, spinel lithium manganese oxide also faces some challenges in practical applications. First, its performance in the 3V range is poor, making it difficult to use as an effective positive electrode material in this voltage range. At the same time, due to its charge and discharge characteristics, a rapid voltage drop occurs in the 3V to 4V range, resulting in a discontinuous voltage curve, which may cause insufficient output problems in this range. In addition, spinel lithium manganese oxide has poor cycle stability under high temperature conditions and is prone to capacity decay. This is mainly because manganese ions are easily dissolved into the electrolyte during the charge and discharge process, resulting in the destruction of the structure of the positive electrode material.

[0004] In summary, spinel lithium manganese oxide has broad application prospects as a positive electrode material for lithium-ion batteries, but its performance improvement still needs to rely on continuous research and innovation in the fields of materials science and electrochemistry to meet the growing market demand. Summary of the invention

[0005] In order to further optimize the performance of lithium-ion batteries containing spinel lithium manganese oxide, the present invention proposes a lithium-ion battery, in which a double-layer positive electrode active material layer is set in the positive electrode, and the thickness ratio and mass ratio of the second positive electrode active material layer to the first positive electrode active material layer are controlled, and the synergistic effect of lithium-rich manganese and lithium manganate is achieved through the double-layer positive electrode active material layer, thereby improving the performance of the lithium battery and enhancing the structural stability. At the same time, lithium supplementation materials are added to the positive electrode to improve the rate performance and electrochemical stability of the battery. The technical solution of the present invention is specifically implemented as follows:

[0006] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, wherein the first positive electrode active material layer is located between the positive electrode current collector and the second positive electrode active material layer;

[0007] The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (0.8:1)-(1.2:1).

[0008] Preferably, the first positive electrode active material layer includes spinel manganese oxide, and the second positive electrode active material layer includes layered lithium manganese oxide and a third positive electrode active material.

[0009] Preferably, the mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide is (1:0.1)-(1:10); preferably (1:0.4)-(1:0.8);

[0010] Preferably, the mass ratio of the layered lithium manganese oxide to the third positive electrode active material is (1:3)-(1:10); preferably (1:5)-(1:6).

[0011] Preferably, the spinel manganese oxide has a structural formula of Li 1+b Mn 2-b-c M c O 4-a Q a ;

[0012] Among them, 0≤a≤1, 0≤b≤0.3, 0≤c≤1;

[0013] M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr, Zn;

[0014] Q includes at least one of the following elements: N, F, S, and Cl.

[0015] Preferably, the layered lithium manganese oxide has a structural formula of dLi2MnO3-(1-d)LiZO2, wherein 0≤d≤1;

[0016] Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti, and B 。

[0017] Preferably, the third positive electrode active material comprises at least one of the following structural formulas: Li 4-x Mn 5- 2x Co 3x O 12 and LiFe 1-y R y R' z XO4;

[0018] Among them, 0.1≤x≤0.5, 0≤y<0.5, 0 <z<1;

[0019] R includes any one of the following elements: Sc, Ti, Cr and V;

[0020] R' comprises at least one of transition metal elements;

[0021] X includes at least one of the following elements: P, Si, S, As and Sb;

[0022] Preferably, R' is iron.

[0023] Preferably, the R further includes at least one of the following elements: Mn, Ni, Co, Cu and Zn.

[0024] Preferably, the positive electrode further comprises a positive electrode lithium replenishing material, the positive electrode lithium replenishing material is arranged in the first positive electrode active material layer or the second positive electrode active material layer, and the mass percentage of the positive electrode lithium replenishing material in the first positive electrode active material layer or the second positive electrode active material layer is n,0 <n≤8%。

[0025] Preferably, the lithium ion battery is a solid-state lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode.

[0026] The present invention proposes an innovative lithium-ion battery design, in which a double-layer positive electrode active material layer is provided in the positive electrode, and the thickness ratio and mass ratio of the second positive electrode active material layer to the first positive electrode active material layer are controlled, so as to improve the performance of the lithium battery and enhance the structural stability. By using layered lithium manganese oxide compounds to provide additional lithium to the spinel lithium manganese oxide, it can operate stably within the range of 3V and be used stably within the range of 3V-4V, avoiding a sharp voltage drop. Therefore, the double-layer positive electrode active material layer promotes the synergistic effect of lithium-rich manganese and lithium manganate, and improves the overall performance of the battery. Secondly, in the low SOC range, the resistance of lithium-rich manganese increases sharply, and by doping lithium iron phosphate or Co-doped Li4Mn5O 12 , since the operating voltage of these materials is slightly lower than that of layered lithium manganese oxide, it can assist in reducing its power in the low range, and therefore has a platform potential curve at a voltage lower than the operating voltage end region of layered lithium manganese oxide, thereby extending the life of the lithium battery and improving its performance. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.

[0029] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0030] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0031] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0032] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0033] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0034] The positive electrode material of manganese-based lithium-ion batteries usually uses spinel-structured LiMn2O4. During the charge and discharge process, lithium ions are embedded and de-embedded between the positive and negative electrodes, accompanied by the redox reaction of manganese ions. Specifically, during the charge process, lithium ions are de-embedded from the LiMn2O4 positive electrode, and manganese ions are de-embedded from the Mn 3+ Oxidized to Mn 4+ During discharge, lithium ions are re-embedded into the positive electrode, and manganese ions are transferred from Mn 4+ Reduction to Mn 3+ . This redox reaction provides the electrochemical energy of the battery. However, under high temperature and deep charge and discharge conditions, the capacity of LiMn2O4 will decay rapidly. This is mainly due to the dissolution of manganese ions in the electrolyte, resulting in the loss of active materials. Secondly, during the cycle process, the lattice structure of LiMn2O4 will be distorted, especially at high voltages. This distortion will lead to a decrease in the mechanical stability of the material, thereby affecting the cycle life of the battery. In addition, oxygen defects in LiMn2O4 will affect the diffusion path of lithium ions and electrochemical properties. The presence of oxygen defects will lead to a decrease in the discharge capacity of the material and deteriorate the electrochemical performance.

[0035] In order to solve the above problems, the present invention proposes a lithium-ion battery, which includes a positive electrode, a negative electrode and an electrolyte. The positive electrode includes a positive electrode collector, a first positive electrode active material layer and a second positive electrode active material layer; the positive electrode collector is used to collect and conduct current, and is usually made of aluminum foil. The first positive electrode active material layer is a layer of material directly coated on the positive electrode collector, which is mainly responsible for the electrochemical reaction of the battery; it is usually made of materials such as lithium metal oxide; the second positive electrode active material layer is located on the first positive electrode active material layer to further enhance the performance of the battery. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (0.8:1)-(1.2:1),

[0036] The present invention optimizes the electrochemical performance of the battery by controlling the thickness ratio of the two layers of positive electrode active material layers. The optimized performance includes capacity, cycle life and rate performance. In addition, the above thickness ratio helps to improve the structural stability of the battery and prevent performance degradation caused by expansion and contraction of the material during charging and discharging, thereby extending the life of the battery.

[0037] In practical applications, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer can be selected as 0.8:1, 0.9:1, 1.0:1, 1.1:1 and 1.2:1, and the above values ​​are only examples and are not limiting.

[0038] In some embodiments, the first positive electrode active material layer includes spinel manganese oxide, and the second positive electrode active material layer includes layered lithium manganese oxide and a third positive electrode active material.

[0039] The spinel structure of spinel manganese oxide provides good ion conductivity and structural stability, and the layered structure of lithium manganese oxide facilitates the insertion and extraction of lithium ions. The third positive electrode active material has high energy density and good thermal stability and is widely used in high-performance lithium-ion batteries.

[0040] In some embodiments, the mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide is (1:0.1)-(1:10).

[0041] In practical applications, the mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide can be selected from 1:0.1, 1:0.4, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, and the above values ​​are only examples and are not limited.

[0042] In some preferred embodiments, the mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide is (1:0.4)-(1:0.8).

[0043] In practical applications, the mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide can be 1:0.4, 1:0.5, 1:0.6, 1:0.7 and 1:0.8, and the above values ​​are only examples and are not limiting.

[0044] In some embodiments, the mass ratio of the layered lithium manganese oxide to the third positive electrode active material is (1:3)-(1:10).

[0045] In practical applications, the mass ratio of the layered lithium manganese oxide to the third positive electrode active material can be selected from 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, and the above values ​​are only examples and are not limiting.

[0046] In some preferred embodiments, the mass ratio of the layered lithium manganese oxide to the third positive electrode active material is (1:5)-(1:6).

[0047] In practical applications, the mass ratio of the layered lithium manganese oxide to the third positive electrode active material can be 1:5, 1:1.55 and 1:6. The above values ​​are only examples and are not limiting.

[0048] In some embodiments, the spinel manganese oxide has a structural formula of Li (1+b) Mn 2-b-c M c O 4-a Q a ;

[0049] Among them, 0≤a≤1, 0≤b≤0.3, 0≤c≤1;

[0050] M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr and Zn;

[0051] Q includes at least one of the following elements: N, F, S, and Cl.

[0052] In some embodiments, the layered lithium manganese oxide has a structural formula of xLi2MnO3-(1-d)LiZO2;

[0053] Among them, 0≤d≤1;

[0054] Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti and B.

[0055] In some embodiments, the third positive electrode active material includes at least one of the following structural formulas: Li 4-x Mn5-2x Co 3x O 12 and LiFe 1-y R y R' z XO4;

[0056] Among them, 0.1≤x≤0.5, 0≤y<0.5, 0 <z<1;

[0057] R includes any one of the following elements: Sc, Ti, Cr and V;

[0058] R' comprises at least one of transition metal elements; preferably iron;

[0059] X includes at least one of the following elements: P, Si, S, As, and Sb.

[0060] In some preferred embodiments, the R further comprises at least one of the following elements: Mn, Ni, Co, Cu and Zn.

[0061] In some embodiments, the positive electrode further includes a positive electrode lithium supplement material, and the positive electrode lithium supplement material is disposed in the first positive electrode active material layer or the second positive electrode active material layer, and the proportion of the positive electrode lithium supplement material is 0-8%.

[0062] The present invention can provide additional lithium ions by adding lithium supplementing materials into the positive electrode, thereby improving the energy density and cycle performance of the battery.

[0063] In practical applications, the proportion of the positive electrode lithium supplement material in the first positive electrode active material layer or the second positive electrode active material layer can be selected from 1%, 2%, 3%, 4%, 5%, 6%, 7% and 8%. The above values ​​are only examples and are not limiting.

[0064] In some embodiments, the positive electrode lithium supplement material includes at least one of the following compounds: lithium cobalt oxide, lithium nickel oxide, lithium ferrite, and Li2O2.

[0065] It can be understood that, whether it is the first positive electrode active material layer or the second positive electrode active material layer, optionally, the positive electrode active material in the positive electrode can be doped with one or more conductive agents that provide electronic conduction and / or at least one polymer binder material that improves the structural integrity of the positive electrode.

[0066] For example, optionally, the positive electrode active material can be mixed with a binder such as poly (tetrafluoroethylene) (PTFE), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate and combinations thereof. The conductive agent may include carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, superP, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, and the like. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.

[0067] The first positive electrode active material layer and the second positive electrode active material layer may independently include greater than or equal to about 50% by weight to less than or equal to about 97% by weight of a positive electrode active material, optionally greater than or equal to about 0% by weight to less than or equal to about 60% by weight of a solid electrolyte, optionally greater than or equal to about 0% by weight to less than or equal to about 15% by weight of a conductive agent, and optionally greater than or equal to about 0% by weight to less than or equal to about 10% by weight of a binder.

[0068] In a specific application, the lithium ion battery is a solid-state lithium ion battery, and the electrolyte may be a solid electrolyte. The solid electrolyte may include one or more solid electrolyte particles;

[0069] Preferably, the solid electrolyte particles may include one or more polymer components, oxide particles, sulfide particles, halide particles, borate particles, nitride particles or hydride particles. When polymer particles are used, lithium salts may be used for double nucleation.

[0070] As an embodiment, the polymer-based component may include one or more polymer materials selected from the group consisting of polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene oxide) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof. In one variation, the one or more polymer materials may have a molecular weight equal to about 10 -4 S / cm ionic conductivity.

[0071] As an embodiment, the oxide particles may include one or more of garnet ceramics, LISICON type oxides, NASICON type oxides, and perovskite type ceramics.

[0072] For example, the one or more garnet ceramics may be selected from the group consisting of:

[0073] Li 6.5 LqCy 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 LqCy 1.75 Nb 0.25 O 12 , Li 6.75 LqCy 1.75 Nb 0.25 O 12 and their combinations.

[0074] The one or more LISICON type oxides may be selected from the group comprising:

[0075] Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4(where 0 <x<1)、Li 3+x Ge x V 1-x O4 (where 0<

[0076] One or more NASICON-type oxides may be defined by LiMM′(PO 4 ) 3 , wherein M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr and La.

[0077] For example, in certain variations, one or more NASICON-type oxides may be selected from the group consisting of:

[0078] Li 1+x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2), Li 1+xAl x Ti 2-x (PO4)3(LATP)

[0079] (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3(LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof.

[0080] One or more perovskite-type ceramics may be selected from the group consisting of the following:

[0081] Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60

[0082] < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25), and combinations thereof. In one variant, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10 -5 S / cm to less than or equal to about 10 -1 S / cm.

[0083] As one implementation, the sulfide-based particles may include one or more sulfide-based materials selected from the group consisting of the following:

[0084] Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 、Li 9.6 P3S 12、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 、Li(Si 0.5 Sn 0.5 )PsS 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 , (1-x) P2S 5-x Li2S (where 0.5≤x≤0.7) and combinations thereof. In one variation, one or more sulfide-based materials may have a carbon content greater than or equal to about 10 -7 S / cm to an ionic conductivity of less than or equal to about 1 S / cm.

[0085] As an embodiment, the halide-based particles may include one or more halide-based materials selected from the group consisting of:

[0086] Li2CdC l4 、Li2MgC l4 、Li2Cd I4 , Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x(where 0 < x < 1) and combinations thereof. In one variation, one or more halide-based materials may have an ionic conductivity greater than or equal to about 10 - 8 S / cm and less than or equal to about 10 -1 S / cm.

[0087] As one implementation, the borate-based particles may include one or more borate-based materials selected from the group consisting of:

[0088] Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variation, one or more borate-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm and less than or equal to about 10 -2 S / cm.

[0089] As one implementation, the nitride-based particles may include one or more nitride-based materials selected from the group consisting of:

[0090] Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variation, one or more nitride-based materials may have an ionic conductivity greater than or equal to about 10 -9 S / cm and less than or equal to about 1 S / cm.

[0091] As one implementation, the hydride-based particles may include one or more hydride-based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4-LiX (where X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4-LiNH2, and combinations thereof. In one variation, one or more hydride-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm and less than or equal to about 10 -2 S / cm.

[0092] It should be noted that the "one or more" claimed in the present invention means that those skilled in the art can selectively choose the material of the double-layer positive electrode active material layer according to actual needs and factors such as the price of raw materials. Whether it is one, two, or even more, it does not change its function and effect of improving the performance of lithium batteries. The present invention only exemplifies rather than limits the types of these materials. In actual applications, materials with the same or similar properties as the above materials can also be selected as the double-layer positive electrode active material layer.

[0093] The embodiments of the present invention will be described in more detail below through examples and comparative examples. It should be noted that the embodiments of the present invention are not limited to these examples.

[0094] Example 1

[0095] A lithium ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, and the negative electrode and the electrolyte are conventional materials.

[0096] The material selection method for the positive electrode is as follows:

[0097] 1. The first positive electrode active material layer structure is composed of LiMn2O4 (96%) + super-P (2%) + PVDF (2%).

[0098] 2. The second positive electrode active material layer structure is composed of 0.5Li2MnO3·0.5LiNi 0.4 Mn 0.6 O2(83%)+Li 3.5 Mn4Co 1.5 O 12 (12%)+PVDF(2%)+super-P(3%)

[0099] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 1:1.

[0100] The positive electrode, negative electrode and electrolyte of the lithium battery described above are all prepared using conventional techniques, and the preparation method is the same as that in Example 1.

[0101] Example 2

[0102] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, the negative electrode and the electrolyte are conventional materials, and the material selection method of the positive electrode is as follows:

[0103] 1. The first positive electrode active material layer structure is composed of LiMn2O4 (96%) + super-P (2%) + PVDF (2%).

[0104] 2. The second positive electrode active material layer structure is composed of 0.5Li2MnO3·0.5LiNi 0.4 Mn 0.6 O2(83%)+LiTi 0.1 Fe 0.9 PO4(12%)+PVDF(2%)+super-P(3%)

[0105] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 1:1.

[0106] The positive electrode, negative electrode and electrolyte of the lithium battery described above are all prepared using conventional techniques, and the preparation method is the same as that in Example 1.

[0107] Comparative Example 1

[0108] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, the negative electrode and the electrolyte are conventional materials, and the material selection method of the positive electrode is as follows:

[0109] 1. The first positive electrode active material layer structure is composed of LiMn2O4 (96%) + super-P (2%) + PVDF (2%).

[0110] 2. The second positive electrode active material layer structure is composed of 0.5Li2MnO3·0.5LiNi 0.4 Mn 0.6 O2(83%)+LiFePO4(12%)+PVDF(2%)+super-P(3%).

[0111] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 1:1.

[0112] The positive electrode, negative electrode and electrolyte of the lithium battery described above are all prepared using conventional techniques, and the preparation method is the same as that in Example 1.

[0113] Comparative Example 2

[0114] A lithium ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, and the negative electrode and the electrolyte are conventional materials.

[0115] The material selection method for the positive electrode is as follows:

[0116] 1. The first positive electrode active material layer structure is composed of LiMn2O4 (96%) + super-P (2%) + PVDF (2%).

[0117] 2. The second positive electrode active material layer structure is composed of 0.5Li2MnO3·0.5LiNi 0.4 Mn 0.6 O2(83%)+Li4Mn5O 12 (12%)+PVDF(2%)+super-P(3%);

[0118] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 1:1.

[0119] The positive electrode, negative electrode and electrolyte of the lithium battery described above are all prepared using conventional techniques, and the preparation method is the same as that in Example 1.

[0120] Comparative experiment:

[0121] Take four groups of samples, namely, Example 1, Example 2, Comparative Example 1 and Comparative Example 2, with 10 samples in each group. Perform power tests on samples in all groups, and take an average value of the test results.

[0122] The power test process is as follows:

[0123] 1. Under 25℃±2℃ environment, discharge at 0.33C constant current to the lower limit voltage and keep it still for 1h;

[0124] 2. Under 25℃±2℃ environment, charge at 0.33C constant current and constant voltage to the upper limit voltage, cut-off current 0.05C, and rest for 1h;

[0125] 3. Under 25℃±2℃ environment, discharge at 0.33C constant current to the lower limit voltage, and let it rest for 1h. The capacity is recorded as C0;

[0126] 4. Under 25℃±2℃ environment, charge at 0.33C constant current and constant voltage to the upper limit voltage, cut-off current 0.05C, and rest for 1h;

[0127] 5. Leave the battery at the target temperature until the battery reaches the target temperature ±2°C;

[0128] 6. Discharge at a specified rate and constant current to the target SOC, and then rest for 1 hour (specified rate: <10℃, discharge rate is 1 / 6C; ≥10℃, discharge rate is 1 / 3C);

[0129] 7. (Xc) Discharge for 10 seconds and let stand for 10 minutes (test current method);

[0130] 8. Charge the battery at the specified rate to the target SOC and leave it for 10 minutes; (>0℃, the specified rate is 0.05C; ≤0℃, the specified rate is 0.01C);

[0131] 9. Repeat steps 7 to 8 until the voltage reaches the lower limit voltage or the maximum discharge rate.

[0132] The final test results are shown in the following table:

[0133]

[0134] According to the above table, LiTi 0.1 Fe and Li 3.5 Mn4Co1.5 O 12 It has a good supporting effect on the positive electrode system, making up for the problem of low power caused by the extremely increased internal resistance of the lithium manganese oxide system under low SOC conditions.

[0135] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, wherein the first positive electrode active material layer is located between the positive electrode current collector and the second positive electrode active material layer; The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (0.8:1)-(1.2:1).

2. The lithium-ion battery according to claim 1, characterized in that The first positive electrode active material layer includes spinel manganese oxide, and the second positive electrode active material layer includes layered lithium manganese oxide and a third positive electrode active material.

3. The lithium-ion battery according to claim 2, characterized in that: The mass ratio of the spinel lithium manganese oxide to the layered lithium manganese oxide is (1:0.1)-(1:10); preferably (1:0.4)-(1:0.8).

4. The lithium-ion battery according to claim 2, characterized in that: The mass ratio of the layered lithium manganese oxide to the third positive electrode active material is (1:3)-(1:10); preferably (1:5)-(1:6).

5. The lithium-ion battery according to claim 2, characterized in that: The spinel manganese oxide has a structural formula of Li 1+ b Mn 2-b-c M c O 4-a Q a ; Among them, 0≤a≤1, 0≤b≤0.3, 0≤c≤1; M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr, Zn; Q includes at least one of the following elements: N, F, S, and Cl.

6. The lithium-ion battery according to claim 2, characterized in that: The structural formula of the layered lithium manganese oxide is dLi2MnO3-(1-d)LiZO2, wherein 0≤d≤1; Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti and B.

7. The lithium ion battery according to claim 2, characterized in that: The third positive electrode active material includes at least one of the following structural formulas: Li 4-x Mn 5-2x Co 3x O 12 and LiFe 1-y R y R' z XO4; Among them, 0.1≤x≤0.5, 0≤y<0.5, 0 <z<1; R includes any one of the following elements: Sc, Ti, Cr and V; R' comprises at least one of transition metal elements; X includes at least one of the following elements: P, Si, S, As and Sb; Preferably, R' is iron.

8. The lithium-ion battery according to claim 7, characterized in that: The R further includes at least one of the following elements: Mn, Ni, Co, Cu and Zn.

9. The lithium-ion battery according to any one of claims 1 to 8, characterized in that: The positive electrode further includes a positive electrode lithium supplement material, which is disposed in the first positive electrode active material layer or the second positive electrode active material layer, and the mass percentage of the positive electrode lithium supplement material in the first positive electrode active material layer or the second positive electrode active material layer is n,0 <n≤8%。 10. The lithium ion battery according to claim 9, characterized in that: The lithium ion battery is a solid-state lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode.